1974
DOI: 10.1037/h0036493
|View full text |Cite
|
Sign up to set email alerts
|

Effects of teacher sex and student sex on the evaluation of college instructors.

Abstract: This study assessed the influence of faculty sex and student sex in teacher evaluation. Twenty questions from the Instructional Improvement Questionnaire which directly evaluate instructor performance were analyzed using a two-factor analysis of variance. No interactions between faculty sex and student sex were found. Generally, there were no differences between the mean ratings given male and female faculty by male and female students. However, male instructors did receive higher ratings on "spoke understanda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
2

Year Published

1976
1976
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 7 publications
(5 reference statements)
2
29
2
Order By: Relevance
“…Though some studies have shown slightly higher global ratings of instructors to come from female students (Bendig, 1952;Ferber & Huber, 1975;Tieman & Rankin-Ullock, 1985), many more have reported no difference in global ratings made by male and female students (e.g., Isaacson, et al, 1964;Doyle & Whitely, 1974;Elmore & LaPointe, 1974, 1975Wilson & Doyle, 1976). Though some studies have shown slightly higher global ratings of instructors to come from female students (Bendig, 1952;Ferber & Huber, 1975;Tieman & Rankin-Ullock, 1985), many more have reported no difference in global ratings made by male and female students (e.g., Isaacson, et al, 1964;Doyle & Whitely, 1974;Elmore & LaPointe, 1974, 1975Wilson & Doyle, 1976).…”
mentioning
confidence: 99%
“…Though some studies have shown slightly higher global ratings of instructors to come from female students (Bendig, 1952;Ferber & Huber, 1975;Tieman & Rankin-Ullock, 1985), many more have reported no difference in global ratings made by male and female students (e.g., Isaacson, et al, 1964;Doyle & Whitely, 1974;Elmore & LaPointe, 1974, 1975Wilson & Doyle, 1976). Though some studies have shown slightly higher global ratings of instructors to come from female students (Bendig, 1952;Ferber & Huber, 1975;Tieman & Rankin-Ullock, 1985), many more have reported no difference in global ratings made by male and female students (e.g., Isaacson, et al, 1964;Doyle & Whitely, 1974;Elmore & LaPointe, 1974, 1975Wilson & Doyle, 1976).…”
mentioning
confidence: 99%
“…6 See Anderson et al (2005), Basow and Silberg (1987), Bennett (1982), Elmore and LaPointe (1974), Harris (1975), Kaschak (1978), Marsh (1984) or Potvin et al (2009), among others.…”
mentioning
confidence: 99%
“…A large body of research has been conducted on the impact of an instructor's sex on course evaluations, and the findings in this area have been quite mixed (see Feldman, 1993 for an overview of this research). Several studies have found that female professors receive lower ratings than male professors, particularly in the ratings given by male students (Basow and Silberg, 1987;Hamermesh and Parker, 2005;Kaschak, 1978;Kierstead et al, 1988;Lombardo Downloaded by [University of Illinois, Chicago] at 11:02 02 April 2016 andTocci, 1979); however, numerous studies have found no significant differences in ratings of male and female instructors (Basow and Distenfeld, 1985;Basow and Howe, 1987;Bennett, 1982;Elmore and LaPointe, 1974;1975;Freeman, 1994). Moreover, in more recent research, it has been discovered that female instructors receive higher ratings than males on a number of different traits, particularly in the ratings given by female students (Basow, 1995;Centra and Gaubatz, 2000;Tatro, 1995).…”
Section: Discussionmentioning
confidence: 98%